Bioaktivitas ekstrak batang Xylocarpus granatum sebagai anti black spot alternatif pada Litopenaeus vannamei pasca panen - Lanny Kartikasari; Awik Pudji Diah Nurhayati; Edwin Setiawan; Dewi Hidayati; Nova Maulidina Ashuri; Noor Nailis Saadah; Farid Kamal Muzaki; Iska Desmawati (Universitas Gadjah Mada, 2017)
This research was done to explore bioactivity of Xylocarpus granatum’s stem extract as tyrosinase inhibitor for alternative preventing black spot in Litopenaeus vannamei postharvest. In this research, extraction of bioactive compound from X. granatum stem was done by soaking the stem in 96% methanol for 24h at temperature 29°C. The methanol was evaporated by using rotary evaporator at temperature 50°C. The extract was dilute with distillate water at series of dilutions (10%, 30%, 50%, 70%, 90%, and distillate water as the control), and then immersing L. vannamei into X. granatum’s stem extract as much as 10ml for 6h, and finally the data analyzing use the Kruskal Wallis test and the Least Significant Difference (LSD) test with the degree of confident 95%. The result showed that X. granatum’s stem extract is able to prevent a black spot of L. vannamei after harvesting process. Furthermore, concentration of 10 % of extract is an effective concentration for preventing a black spot and the control has black spot 0.0360 – 0.0373 mm2.